THE IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION AT PUBLIC SCHOOLS IN BANGKOK CITY - Wanchai Niyom; Mohamad Ali (Universitas Muhammadiyah Surakarta, 2020)
The purpose of this research is to study and study the management of Islamic education in Bangkok and government schools as well as to formulate recommendations and implementation of Islamic education. The main contributors in this study consisted of 3 interviewees, school teachers Klong Nueng (Kaewnimit) and other government school teachers. Qualitative informants and sources are the head of PAI. And Islamic education teachers in many government schools in Bangkok have mixed research designs using exploratory design models. And content analysis for qualitative data. In the implementation of the Bangkok government school Islamic education curriculum, the overall picture is at a good level. And the implementation of Islamic education from the head of PAI and PAI teachers, there is no difference and work experience. Suggestions and guidelines for the implementation of Islamic education in government schools in the metropolitan area of Bangkok 1) Preparation there must be coaching for the head of the academic field and PAI teachers in the field of recruitment of teachers who have immediately completed Islamic education teaching Islamic education 2) planning for curriculum implementation and implementation of all parties involved in the management of Islamic education. The curriculum must be planned and sustainable. So that the curriculum can be adjusted to the curriculum structure, both subject matter and study time 3) Implementing the implementation of the Islamic education curriculum the teacher must provide instruction. In accordance with the course structure Teaching integrated course content And using various techniques Use interesting materials Media for the teaching and learning process. ) Supervision, monitoring, and evaluation. Within the school, a supervisory committee should be appointed. Joint planning for the supervision of Islamic education. Set of supervision to summarize and report the results of supervision to related parties and the community. And let the agencies carry out their duties in the field of Islamic education to participate in monitoring the management of Islamic education in a sustainable manner